Repartição do ICMS para os municípios paulistas: uma questão de justiça - Teles, Rogério (2015)
The purpose of this research is to enhance the distribution of the ICMs among the São Paulo districts and, mainly, comprehend how the concepts of justice takes place in the division of this taxation. It is a research with theoretical and documentary foundation where we search the references to find aids to answer the guiding question: is there justice on the ICMs division? The data on this work were collected on the reading upon justice, federation, national tributary system, ICMS and its division and analysis grounded on the theoretical references and existing literature regarding the theme. The study was divided into five chapters: justice which reveals its content; federation, tributary system and tribute division; state value-added tax on the circulation of goods and upon interstate and intercity transportation and communication service (ICMS); ICMS divisions; justice and ICMs divisions in the state of São Paulo: new considerations, from which we conclude there is the necessity to reconsider the criteria of the aggregated value by reducing it and benefiting the population, personal tax revenue, cultivated area, flooded area, preserved area and fixed percentage aspects